Physical recovery in the first six months following oesophago-gastric cancer surgery. Identifying rehabilitative needs: a qualitative interview study. Issue 10 (8th May 2021) - O'Neill, Linda; Bennett, Annemarie E.; Guinan, Emer; Reynolds, John V.; Hussey, Juliette
Abstract: Purpose: To investigate patients' perspectives of their physical recovery in the first six months post oesophago-gastric cancer surgery. Materials and Methods: Semi-structured interviews were held at St James's Hospital, Dublin, with participants who were 4 weeks to 6 months post-oesophagectomy/gastrectomy. Interviews were an average of 14 min and included questions pertaining to physical recovery post-oesophagectomy/gastrectomy. Interviews were audio-taped, transcribed verbatim, and analyzed by thematic analysis. Results: Twenty participants (mean age 63.35(7.50) years) were recruited. Four themes were identified: i) challenges of recovery and impact on physical activity, ii) facilitators of, and barriers to, returning to physical activity, iii) physical challenges of returning to pre-operative societal roles, iv) recommendations for health services on measures which may enhance the return to physical activity. Post-operative barriers to physical activity included dietary issues, continuing treatments, pain, breathlessness, muscle weakness, fatigue, and anxiety. Participants identified that strategies such as a gradual return to activities, rest, and family support facilitated return to physical activity. Participants highlighted the need for i) greater physiotherapy input, ii) psycho-social support, and iii) fatigue management may aid physical recovery: Conclusions: Following oesophago-gastric cancer surgery, patients experience physical and psychosocial difficulties which can hamper recovery, but many of which are amenable to rehabilitative intervention. Accordingly, rehabilitative measures throughout the early stages of recovery require investigation. Implications for Rehabilitation: Curative treatment for oesophageal and gastric cancer is associated with significant risk of post-operative morbidity, resulting in a myriad of physical and nutritional challenges which may impact on post-operative physical recovery. Greater provision of physiotherapy services to counteract physical impairments post oesophago-gastric cancer surgery is required. Physical recovery may also be aided through the enhanced provision of other supportive care services such as fatigue management and psychological support.